NEW PUBLIC SERVICE THEORY DALAM REFORMASI ASN INDONESIA: ASN SEBAGAI PELAYAN PUBLIK, BUKAN ALAT POLITIK - Diva Ratna Bila; Sari, Aslinda Gangga; Balirani Hayuningrat; Keisya Hilda Adzania (PARADIGMA: Jurnal Ilmu Administrasi, 2025)
This article discusses the transformation of the role of civil servants in the context of Indonesia's bureaucratic reform through the New Public Service approach, which places citizens at the center of service delivery. This paradigm shift requires the alignment of values, structures, and work culture of the ASN to be more professional, responsive, and free from political influence. The discussion covers three main aspects, namely the shift in the orientation of the ASN towards humanistic public service, the importance of neutrality and depoliticization in maintaining the objectivity of services, and the strengthening of professionalism and performance-based results through innovation and an accountable evaluation system. The results of the study show that the implementation of the NPS principle, a merit system, and the strengthening of ASN competencies are key to producing fair, effective, and integrity-based public services. This article emphasizes that the success of ASN reform depends on policy consistency, institutional commitment, and public involvement in overseeing bureaucratic change.